The link between varicella and immune system: which children will develop acute cerebellitis? - Bozzola, Elena (Ital J Pediatr, 2020)
INTRODUCTION: Varicella may complicate with cerebellitis in previously healthy children, requiring hospitalization. Aim of our study was to define whether children who experienced varicella cerebellitis have a normal immune system. METHODS: Patients over 3 years of age admitted at Bambino Gesù Children from January 2006 till June 2016 for cerebellitis in varicella were asked to participate to the follow-up study. The immune status was evaluated clinically and by laboratory investigations. RESULTS: Twenty-five patients were included in the study. At follow up, at least one immunological alteration was detected in 80% of patients. To avoid bias due to possible effects of the recent disease, we separately analyzed patients who had the follow-up control at least 1 year (Group 1) or between 1 month and 1 year (Group 2) after the hospitalization for acute varicella cerebellitis. The results were similar in both groups with immunological alterations detected in 84,6 and 75% of the patients, respectively. CONCLUSIONS: Our preliminary results indicate that sub-clinical immunological defects may correlate to cerebellitis in varicella.